2023
DOI: 10.3390/cancers15225313
|View full text |Cite
|
Sign up to set email alerts
|

Long Non-Coding RNA LOC339059 Attenuates IL-6/STAT3-Signaling-Mediated PDL1 Expression and Macrophage M2 Polarization by Interacting with c-Myc in Gastric Cancer

Haibo Han,
Guangyu Ding,
Shanshan Wang
et al.

Abstract: Background: Long non-coding RNA (lncRNA) was identified as a novel diagnostic biomarker in gastric cancer (GC). However, the functions of lncRNAs in immuno-microenvironments have not been comprehensively explored. In this study, we explored a critical lncRNA, LOC339059, that can predict the clinical prognosis in GC related to the modulation of PD-L1 and determined its influence upon macrophage polarization via the IL-6/STAT3 pathway. Methods: To date, accumulating evidence has demonstrated that the dysregulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…These results are consistent with those reported in other studies. In addition, mauer et al reported that IL-6 signalling promotes macrophage M2 polarization to reduce pronounced inflammation and insulin resistance, and identified IL-6 signalling as an important determinant of macrophage M2 polarization [ 40 , 41 ]. Hence, the regulation of macrophage M2-type polarization by Mg–Ca/nHAC biomaterials may involve a more intricate process that needs to be explored in the future.…”
Section: Discussionmentioning
confidence: 99%
“…These results are consistent with those reported in other studies. In addition, mauer et al reported that IL-6 signalling promotes macrophage M2 polarization to reduce pronounced inflammation and insulin resistance, and identified IL-6 signalling as an important determinant of macrophage M2 polarization [ 40 , 41 ]. Hence, the regulation of macrophage M2-type polarization by Mg–Ca/nHAC biomaterials may involve a more intricate process that needs to be explored in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Decrease in the levels of interleukin-6 also exerts inhibitory effects on interleukin-mediated JAK/STAT3 signaling and consequent suppression of PD-L1. Moreover, polarization of macrophages into M2 phenotype was also effectively reduced [ 61 ].…”
Section: Lncrnas Activate Stat3 Signaling and Induce Polarization Of ...mentioning
confidence: 99%